Nutritional constraints to grazing ruminants in the millet-cowpea- livestock farming system of the Sahel - Fernández Rivera, S.; Hiernaux, Pierre H.Y.; Williams, Timothy O.; Turner, M.; Schlecht, Eva; Salla, A.; Ayantunde, Augustine A.; Sangare, M. (International Livestock Research Institute, 2005)
Growing pearl millet and cowpea in combination with raising ruminant livestock is widely practiced in the Sahel. In this farming system, livestock feeding depends mostly on rangeland, fallows and cropland grazing. Nutritional constraints to grazing ruminants stem primarily from feed scarcity and seasonal fluctuations in feed supply associated with low rainfall and poor soil fertility. Low feed quality exacerbates the effects of feed scarcity and seasonality. Some herd management practices result in decreased grazing times and feed intake and (or) increased energy expenditures for walking. Land tenure and use tights, among other socioeconomic factors, constrain the nutrition of livestock by limiting herd mobility and access to feed resources. Expansion of copping areas onto rangeland may result in higher overall feed yields but limits feed availability and access to grazing lands during the rainy season. Nutrition of livestock can be improved with better herd and range management practices, increasing the quantity and quality of feed produced on range and cropland and by using feed supplements. These options need to be profitable and compatible with the resource endowment and production objectives to be adopted by farmers. Policies and institutional arrangements are also required to facilitate herd mobility and access to water and grazing land and to solve and prevent conflicts among users of these resources.